A REVIEW ON IMAGE REGISTRATION TECHNIQUES FOR BLUR REMOVAL - Pramila Sanga (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The original method utilizes the phase of the images and has its roots on phase correlation (PC) registration. The even powers of the normalized Fourier transform of an image are invariant to centrally symmetric blur, such as motion or out-of-focus blur. Then use these results to propose blur-invariant phase correlation. The method has been compared to PC registration with excellent results. The method works for unknown blurs assuming the blurring PSF exhibits an N-fold rotational symmetry. It does not require any landmarks. We explicitly address only registration with respect to translation, but the method can be readily generalized to rotation and scaling. Now we also generalize the theory to the case of dihedrally symmetric blurs, which are produced by the PSFs having both rotational and axial symmetries. Such kind of blurs is often found in unfocused images acquired by digital cameras, as in out-of-focus shots the PSF typically mimics the shape of the shutter aperture. This makes our registration algorithm particularly well-suited in applications where blurred image registration must be used as a preprocess step of an image fusion algorithm, and where common registration methods fail, due to the amount of blur. We demonstrate that the proposed method leads to an improvement of the registration performance, and we show its applicability to real images by providing successful examples of blurred image registration followed by depth-of-field extension and multichannel blind deconvolution.